Spatial and temporal replicability of meteoric and in situ ¹Be concentrations in fluvial sediment - Sosa,Gonzalez V; Schmidt,AH; Bierman,PR; Rood,DH (Earth Surface Processes and Landforms, 2017)
Cosmogenic isotopes, short-lived radionuclides, elemental concentrations and thermochronometric indicators are measured in river sand to quantify erosion rates and trace sediment sources, and/or infer erosional processes. Interpretations of detrital sediment analyses are often based on the rarely tested assumption of time-invariant tracer concentration. A better understanding of when and where this assumption breaks down and what sampling strategies minimize temporal and small-scale spatial variance will improve science done using detrital river sediment. Here, we present new and previously published spatial and temporal replicates measured for in situ and meteoric 10 Be ( 10 Be i and 10 Be m , respectively). Our new data include 113 replicate pairs, taken from agricultural and/or tectonically active watersheds in China months to millennia apart and spatial replicates taken up to 2 km apart on the same day. The mean percentage difference is 10% (-122% to 150%) for both systems considered together; the mode is close to 0% for both systems; and 36% of pairs of samples replicate within our analytical accuracy at 2σ. We find that 10 Be i replicates better than 10 Be m (p < 0.01). 10 Be i replicability is worse in steeper basins, suggesting that stochastic processes (i.e. landslides) affect reproducibility. 10 Be m replicability is worse in larger basins, suggesting non-conservative behavior of 10 Be m as sediment moves downstream. Our results are consistent with the few previously published replicate studies. Considering all replicate data in a wide range of landscapes, in areas with deep erosional processes, replicability is poor; in other areas, replicability is good. This suggests that, in steep, tectonically active, and/or agricultural landscapes, individual detrital sediment measurements do not represent upstream rates as well as larger populations of samples. To ensure that measurements are representative of the upstream watershed, our data